HUBUNGAN TINGKAT PENDIDKAN IBU DENGAN KEBIASAAN MEMBERIKAN MP-ASI USIA 6-24 BULAN DI DESA FATUMNASI KECAMATAN FATUMNASI KABUPATEN TIMOR TENGAH SELATAN - Yohanes Don Bosko Demu; Astuti Nur; Tresha Efatasia Indah Keo (Kupang Journal of Food and Nutrition Research, 2022)
MP-ASI is a transitional food from breast milk to family food given to children aged 6-24 months gradually by type, frequency of administration, number of servings and forms of food that are adapted to the baby's age and ability to digest food to meet their nutritional needs. This study aims to determine the relationship between the level of maternal education and the habit of giving complementary food aged 6-24 months in Fatumnasi Village, Fatumnasi District, South Central Timor Regency. This research is a quantitative study with a cross sectional design. The samples in this study were 30 baduta aged 6-24 months in Fatumnasi Village.Based on the results of the study, it was obtained that there was a relationship between the level of maternal education and the habit of giving complementary food aged 6-24 months in Fatumnasi Village, Fatumnasi District, South Central Timor Regency with a p-value = 0.037 <0.05. It is recommended to further research and develop several influencing factors in the administration of complementary food so that complementary food is given appropriately.